Iman, Akal, Dan Kemanusiaan: Titik Temu Pendidikan Kristen Dan Fikrah Islamiyyah Dalam Penguatan Moderasi Beragama - Urbanus Sukri (Yayasan Azhar Amanaa Yogyakarta, 2026)
The increasing challenges of intolerance, radicalism, and identity polarization in pluralistic societies call for the development of an educational paradigm capable of strengthening religious moderation in a substantive and sustainable manner. This article aims to analyze the common ground between Christian education and Fikrah Islamiyyah through the concepts of faith, reason, and humanity as the foundation for promoting religious moderation. This study employs a qualitative approach using library research and a philosophical-comparative analysis of primary and secondary literature related to the philosophy of Christian education, Islamic educational thought, and the concept of religious moderation. The findings reveal that both educational traditions share fundamental perspectives in viewing faith as the source of values and moral orientation, reason as an instrument for seeking truth and developing knowledge, and humanity as the sphere for actualizing religious values in social life. The concept of imago Dei in Christian education and karāmah al-insān in Fikrah Islamiyyah demonstrate substantial similarities in affirming human dignity. Furthermore, the integration of faith and reason in both traditions produces an educational paradigm that rejects the dichotomy between religion and science while fostering an inclusive, dialogical, and responsible religious attitude. This study concludes that faith, reason, and humanity constitute shared conceptual foundations that can be developed as a framework for religious moderation education. These findings contribute to the advancement of interfaith education studies and offer a humanistic, transformative, and relevant educational model for multicultural societies in the twenty-first century.